The impact of heat waves on electricity spot markets - Anna Pechan; Klaus Eisenack (University of Oldenburg, Department of Economics, 2013)
Thermoelectric power plants depend on cooling water drawn from water bodies. Low river run-off and/or high water temperatures limit a plant's production capacity. This problem may intensify with climate change. To what extent do such capacity reductions affect electricity spot markets? Who bears the consequent costs? How is this influenced by climate change and a change in the electricity generation system? We quantify these effects by means of a bottom-up power generation system model. First, we simulate the German electricity spot market during the heat wave in 2006, and then conduct a sensitivity study that accounts for future climatic and technological conditions. We find an average price increase of 11%, which is even more pronounced during times of peak demand. Production costs accumulate to additional but moderate e15.9 m during the two week period. Due to the price increase producers gain from the heat wave and consumers disproportionately bear the costs. Carbon emissions increase during the heat wave. The price and cost effects are more pronounced and significantly increase if assumptions on heat-sensitive demand, hydro power capacity, net exports and capacity reductions are tightened. These are potential additional effects of climate change. Hence, if mitigation fails or is postponed globally, the impacts on the current energy system are very likely to rise. Increases in feed-in from renewable resources and demand-side management can counter the effects to a considerable degree. Countries with a shift to renewable energy supply can be expected to be much less susceptible to water scarcity than those with a high share of nuclear and coal-fired power plants.
Keywords: Q41; Q54; 330; Electricity Market; Heat Wave; Germany; Climate Change; Strompreis; Spotmarkt; Klimawandel; Schock; Kraftwerk; Deutschland